2020
DOI: 10.1186/s13045-020-00941-y
|View full text |Cite
|
Sign up to set email alerts
|

A single-cell survey of cellular hierarchy in acute myeloid leukemia

Abstract: Background Acute myeloid leukemia (AML) is a fatal hematopoietic malignancy and has a prognosis that varies with its genetic complexity. However, there has been no appropriate integrative analysis on the hierarchy of different AML subtypes. Methods Using Microwell-seq, a high-throughput single-cell mRNA sequencing platform, we analyzed the cellular hierarchy of bone marrow samples from 40 patients and 3 healthy donors. We also used s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 98 publications
2
47
0
Order By: Relevance
“…The accumulation of increasingly abundant single-cell sequencing data enabled establishment of The Cancer Cell Atlas, which covers a spectrum of cancers (Table 2 ). For example, Microwell-Seq contributed to cellular hierarchy construction and clonal heterogeneity deciphering in normal bone marrow and acute myeloid leukemia [ 69 ]. By integrating clinical pathological information and single-cell sequencing data, novel diagnostic and prognostic biomarkers and potential therapeutically relevant cell types or states could be deciphered [ 70 ].…”
Section: Applications Of Single-cell Sequencing In Cancer Biologymentioning
confidence: 99%
“…The accumulation of increasingly abundant single-cell sequencing data enabled establishment of The Cancer Cell Atlas, which covers a spectrum of cancers (Table 2 ). For example, Microwell-Seq contributed to cellular hierarchy construction and clonal heterogeneity deciphering in normal bone marrow and acute myeloid leukemia [ 69 ]. By integrating clinical pathological information and single-cell sequencing data, novel diagnostic and prognostic biomarkers and potential therapeutically relevant cell types or states could be deciphered [ 70 ].…”
Section: Applications Of Single-cell Sequencing In Cancer Biologymentioning
confidence: 99%
“…In this study, we characterized the immune components of different AML patient-derived BM cells by sc-RNAseq data analysis. Different from concentrating on analysis of clonal heterogeneity and hierarchies of AML cells [ 31 , 32 ], we focused on the mature immune cell types and immune status under the stress of AML and chemotherapy. To assess the composition, function, and status of immune cells, we performed scRNA-seq analysis using publicly-available datasets (GSE116256) [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acute myeloid leukemia (AML) is a disease which is characterized by clonal proliferation and is derived from primitive hematopoietic stem cells or progenitor cells. It has an extremely high mortality and poor prognosis in elderly patients (116,117). Cytogenetic analysis revealed that there are a large number of non-random chromosomal abnormalities in AML, with about 60% of adult AML patients being diagnosed with gene abnormalities (118).…”
Section: Txnip and Leukemiamentioning
confidence: 99%